2017
DOI: 10.1016/j.psyneuen.2016.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase and acetyltransferase inhibitors modulate behavioral responses to social stress

Abstract: Histone acetylation has emerged as a critical factor regulating learning and memory both during and after exposure to stressful stimuli. There are drugs that we now know affect histone acetylation that are already in use in clinical populations. The current study uses these drugs to examine the consequences of acutely increasing or decreasing histone acetylation during exposure to social stress. Using an acute model of social defeat in Syrian hamsters, we systemically and site-specifically administered drugs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 49 publications
(78 reference statements)
0
8
0
Order By: Relevance
“…These drugs also reverse social avoidance when administered to the amygdala and PFC (Covington, Maze, Vialou, & Nestler, ; Covington et al., ). Inhibition of HDAC with valproic acid not only increases the effects induced by SD (McCann et al., ), but also the conditioning rewarding effects of cocaine because HDAC inhibitors increase associative learning (Montagud‐Romero, Montesinos et al., ; Ploense et al., ). On the contrary, inhibition of HAT activity with the HAT inhibitor curcuma longa, or through viral‐mediated transfer and overexpression of specific HDACs in the NAc, markedly inhibits the increase in cocaine‐induced CPP in defeated animals (Hui, Wang, & Li, ; Renthal et al., ).…”
Section: Mechanisms Underlying the Effects Of Social Defeat Stress Onmentioning
confidence: 99%
See 1 more Smart Citation
“…These drugs also reverse social avoidance when administered to the amygdala and PFC (Covington, Maze, Vialou, & Nestler, ; Covington et al., ). Inhibition of HDAC with valproic acid not only increases the effects induced by SD (McCann et al., ), but also the conditioning rewarding effects of cocaine because HDAC inhibitors increase associative learning (Montagud‐Romero, Montesinos et al., ; Ploense et al., ). On the contrary, inhibition of HAT activity with the HAT inhibitor curcuma longa, or through viral‐mediated transfer and overexpression of specific HDACs in the NAc, markedly inhibits the increase in cocaine‐induced CPP in defeated animals (Hui, Wang, & Li, ; Renthal et al., ).…”
Section: Mechanisms Underlying the Effects Of Social Defeat Stress Onmentioning
confidence: 99%
“…For example, there are cases in which female rodents exhibit territorial and maternal aggression, which constitutes an avenue for examining sex differences in physiology and behavior in response to stress (Solomon, ). Female rodents are capable of displaying threat and attack behavior, and in some species are more aggressive than males during agonistic encounters (Huhman et al., ; McCann et al., ). Defeated females respond to a caged opponent with similar social avoidance to that observed in males, but research some decades ago showed that female rats do not become “permanently” submissive after losing an aggressive encounter (Brain et al., ; Scholtens, Van Haaren, & Van De Poll, ; Swanson, ).…”
Section: Conclusion: Limitations and Future Directionsmentioning
confidence: 99%
“…These data also demonstrate that measuring conditioned defeat in hamsters that are tested with a freely moving, non-aggressive intruder produces comparable data to that generated in mice using social avoidance of a caged opponent as the dependent measure. Although we have shown that hamsters, like mice, display social avoidance to caged opponents 68,[85][86][87] , conditioned defeat testing in hamsters adds complementary data in that it is possible to measure not only submission and social avoidance, but also to determine if treatments have any effect on aggression. Importantly, we observed no changes in aggressive behavior following any of the treatments used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the IL (in addition to the PrL) is also activated in a shifting social environment in which social ascent is possible, as in the case of removing an alpha male in a mouse hierarchy ( Williamson et al, 2018 ). Administration of a histone deacetylase inhibitor to the IL increases stress behaviors in a Syrian hamster model of social defeat ( McCann et al, 2017 ), further implicating the IL in social interactions involving dominance.…”
Section: Discussionmentioning
confidence: 99%